PERENCANAAN GARDU DISTRIBUSI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TADULAKO - Arifudin Arifudin; Tribianto Tribianto; Muhammad Sarjan; Baso Mukhlis (Foristek, 2020)
The Faculty of Teacher Training and Education is one of the Faculties that has the most buildings in Tadulako University, which of course requires large capacity electrical equipment facilities and also requires large electric power as well. To provide optimal services so that lecture, practicum and other activities are not disrupted due to electrical problems. Electricity problems at the Faculty of Teacher Training and Education are currently caused by excessive loading that is not adjusted to the transformer capacity at the Economic Substation, The distance that is served by the Economic Substation is approximately 950 meters so that it causes losses on the network. Based on the calculation of the total load obtained for lighting, room conditioning and auxiliary contact boxes of 167,402 kVA and considering the addition of Loads and Buildings within the Faculty of Teacher Training and Education, the transformer capacity used is 200 kVA and according to SPLN Transformers with capacities below 200 kVA must use Portal substation construction.